Venetian Heritage twenty years of preserving and promoting Venice's cultural legacy - De Fina, Matteo; Magliani, Mauro 1958- (Rizzoli, 2019)
"Celebrating the twentieth anniversary of Venetian Heritage--whose mission is to safeguard Venetian cultural legacy as manifested in architecture, music, and fine art--this stunning volume highlights the organization's work in restoring, preserving, and promoting the cultural heritage of Venice. This book showcases the most impressive restoration projects of the last twenty years, from the eighteenth-century façade of the Church of Jesuits and early-Renaissance façade of the Church of San Zaccaria in Venice, to the Chapel of the Blessed Giovanni Orsini and the Romanesque portal of the Cathedral of Saint Lawrence in Croatia. Beautifully photographed in breathtaking detail, this volume tells the story of the crucial role that Venetian Heritage has in preserving the art of Venice both in Italy and in the areas once part of the Republic of Venice"--Amazon.com
Keywords: Venetian Heritage Inc.; Geschichte; Geschichte 2000-2020; Kunst; Restaurierung; Venedig; Venetian Heritage Inc / History; Art / Conservation and restoration / Italy / Venice / History; Art / Conservation and restoration / Croatia; Historic buildings / Conservation and restoration / Italy / Venice / History; Historic buildings / Conservation and restoration / Croatia / History; Art / Conservation and restoration; Historic buildings / Conservation and restoration; Italy / Venice; History; Bildband